The Effect of WHA and Lime for Shear Strength of Clay Stabilized by Cement - Nugroho, Soewignjo Agus; Ongko, Andarsin; Fatnanta, Ferry; Putra, Agus Ika (Universitas Negeri Semarang, 2022)
With the use of the additive, the clay's shear strength and bearing capacity increased. Usage waste material, Wooden Hush Ash (WHA), is tiny. The silicate content of WHA is almost the same as RHA. This study aims to utilize ASK for a stabilization material of high plasticity clay to increase shear strength. Unconfined Compression Strength (UCS) tests were performed to compare the UCS value of clay; clay with 5% cement; clay with lime; clay-cement with WHA; clay-cement with lime and WHA; and clay with lime and WHA. Before the UCS test, the sample was separated into two groups: with and without curing for 28 days, and with and without soaking for 4 days. While in conditions unsoaked, the qu value is uniform. Results show, without curing and soaked, qu values of all variations have the same value in the range of 350 kPa to 380 kPa. In conditions with curing 28 days with and without soaked, qu values range from 365 kPa to 485 kPa for mixtures with WHA and a combination of lime with ASK. While adding of 10% lime additive increases the qu value to 1100 kPa UCS testing results prove, with and without curing and soaked, lime is more optimal to increase the value of UCS than WHA. Replacement lime with WHA by 4% to 6% increases the qu value from 160 kPa to 465 kPa and 485 kPa and 110 kPa to 440 kPa to 475 kPa of soaked and unsoaked condition respectively. WHA can be used to reduce lime in soil stabilization.